CORAL REEF RECOVERY FOLLOWING ACANTHASTER INFESTATIONS - Pearson, R. G. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Since late 1971, data have been obtained on coral recolonization on reefs of the Great Barrier Reef which had been damaged by Acanthaster infestations during the 1960's. There is now tabular Acropora, particularly on the seaweed reef slope in the depts of less than 10 meters. Many such corals now measure 50 cm to 100 cm in diameter. However, recent observations indicate that these corals can be dislodged by strong wave action thus providing an opportunity for both further coral settlement and for the survival and growth of previously